Worship and rituals in religion ancient Judaism (Journal of the College of Basic Education, 2022)
The available evidence indicates that the religion of Jehovah mentioned in the Old Testament did not come from abroad with immigrant groups, as this book assumes, but rather developed within the Canaanite religious establishment. the period prior to the Babylonian captivity of Judah; There are no temples to the biblical god Yahweh, no temples, no altars, no inscriptions that mention him the way the biblical books present him. On the other hand, there was a god in Palestine named Jehovah, but he changed Jehovah, the God of the Old Testament, in his importance and attributes